EFEK SUHU TERHADAP PEMBENTUKAN BESARAN BUTIRAN ARANG KARBON TEMPURUNG KELAPA SAWIT - Malik, Usman (Edu Research, 2013)
Research has been carried out using x-ray diffraction analysis and analysisof Atomic Energy Dispersive X-Ray (EDAX) on a sample of oil palm shellcarbon. X-ray diffraction spectrum of a sample of oil palm shell carbon has anamorphous structure with two peaks in the energy intensity of 639 AU and 232AU (Arbitari Unit). The elements contained in the oil palm shell carboncontaining elements other than carbon C amounted to 98.48% of other elementsthat are also contained 0.71% Si silicon. EDAX analysis of the percentageobtained on the building blocks of atomic carbon C is approximately 99.69% and0.31% Si silicon. SEM analysis obtained by cross-sectional shape is irregular, soit can be concluded that oil palm shell carbon is amorphous, and visible changesin the peak position, width and height of the temperature difference diffractogramto the formation of massive carbon charcoal granules.